CELAFISCS’ contributions to sports science and physical activity: a tribute to 50 years of history - Luiz Guilherme Grossi Porto; Guilherme Eckhardt Molina; Lamartine Pereira DaCosta; Isabella Lima Ramos; Felipe Donato Vargas; Laércio Elias Pereira; Américo Pierangeli Costa (Revista Brasileira de Atividade Física e Saúde)
Introduction: The Center of Studies of the Physical Fitness Research Laboratory from Sao Caetano do Sul (Centro de Estudos do Laboratório de Aptidão Física de São Caetano do Sul - CELAFISCS) is a research and intervention center with broad national and international recognition. In 2024, CELAFISCS completes 50 years of uninterrupted activity. Objectives: Based on a theoretical essay, our objective was to promote a tribute to the 50 years of CELAFISCS by recovering its main contributions to the Sports and Physical Activity Sciences. Development: The complex task of summarizing the most relevant contributions of CELAFISCS was carried out through documentary analysis and testimonies in three parts: historical aspects, tangible contributions, and intangible ones. Tangible contributions were analyzed considering the scientific production and human resources training done by the members of the successive boards of CELAFISCS during this period. The intangible contributions were analyzed by the impacts of the rapprochement of Brazilian science with the most influential scientists and institutions in the world, of projects to promote physical activity, such as Agita São Paulo, in addition to the social commitment and vision of the future, which are recognized characteristics of CELAFISCS. Final Considerations: Our findings demonstrate that in these 50 years, CELAFISCS has had an equitable distribution by gender, a predominance of physical education professionals, and a high proportion of members involved in research. CELAFISCS has generated highly significant contributions to Sports and Physical Activity Sciences in Brazil, both in academic production and human resources training, justifying the recognition of its essential importance for developing these two significant areas.